(untitled) - STYORO CAHYO WIBOWO, AGUS (Jurnal Ilmu Manajemen (JIM), 2013)
PT. Perusahaan Listrik Negara (Persero) Area Bojonegoro is astate corporation (BUMN) which holds all the electric power distribution inBojonegoro. The employe performance is one of the measurements thatis often used to measure the company achievement. A company will notbe progressing if the employee performance is not qualified in thebusiness competition. Training and creativity have a god effect on theemployee performance. Therefore, those aspects need to be concernedto improve the employee performance. Hence, the purpose of thisresearch is to test and analyze “the effect of training and creativity on theemployee/technician performance in PT. Perusahaan Listrik Negara(Persero) Area Bojonegoro” both partially and simultaneously. There are42 samples taken from the employees, especially the technician. Thedata analysis method used in this research is the multiple linearregression analysis with the support of SPSS 18 software for windows.The results of the analysis shows that both partially and simultaneouslytraining and creativity have a good impact for the technicians in PT.Perusahaan Listrik Negara (Persero) Area Bojonegoro.Keywords : training, creativity, and employee performance.